2013
DOI: 10.1364/oe.21.017904
|View full text |Cite
|
Sign up to set email alerts
|

Silicon mode multi/demultiplexer based on multimode grating-assisted couplers

Abstract: A simple and low-crosstalk 1 × 4 silicon mode (de)multiplexer based on multimode grating-assisted-couplers is proposed. Mode transitions can be flexibly controlled by designing the grating period at the phase-matching condition. Due to the contra-directional coupling, precise control of the coupling strength and the coupling length are not needed in the system. Calculation results show that the insertion loss and the 3 dB bandwidths of the device are 0.2 dB and 3.7 nm, 0.34 dB and 7.6 nm, and 0.21 dB and 11.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(50 citation statements)
references
References 10 publications
0
49
0
Order By: Relevance
“…[30] Later a grating-assisted ADC was also designed to realize 4-channel narrow-band mode multiplexer. [31] The ADC-based mode (de)multiplexers have also been used to realize hybrid (de)multiplexers by integrating with other WDM devices. For example, a three-channel multiplexer combining ADCs and microrings for simultaneous MDM and WDM has been realized to expand the link capacity.…”
Section: Doi: 101002/lpor201700109mentioning
confidence: 99%
“…[30] Later a grating-assisted ADC was also designed to realize 4-channel narrow-band mode multiplexer. [31] The ADC-based mode (de)multiplexers have also been used to realize hybrid (de)multiplexers by integrating with other WDM devices. For example, a three-channel multiplexer combining ADCs and microrings for simultaneous MDM and WDM has been realized to expand the link capacity.…”
Section: Doi: 101002/lpor201700109mentioning
confidence: 99%
“…1(c). The mode converter-(de)multiplexer can be realized by using an evanescent coupling system designed carefully [28][29][30]. Recently some progress has been made on mode converter-(de)multiplexers based on planar optical waveguides, which will be reviewed below.…”
Section: The Configuration For a Multimode Sdm Optical-interconnect Lmentioning
confidence: 99%
“…[27], we have previously proposed and demonstrated a 4-channel silicon mode converter-multiplexer operating for TM polarization with low loss, low crosstalk as well as small footprint. Recently a gratingassist ADC was designed to construct a 4-channel narrow-band mode converter-multiplexer [28]. In Ref.…”
Section: Mode Converter-multiplexermentioning
confidence: 99%
“…Ding et al have demonstrated an on-chip two-mode division multiplexing circuit using a tapered directional coupler-based TE 0 and TE 1 mode multiplexer and demultiplexer on the silicon-on-insulator platform [6]. In [7], Dai mode (de)multiplexer based on multimode grating-assistedcouplers has been proposed in [8]. Luo et al have shown the first microring-based on-chip WDM-compatible mode-division multiplexing with low modal crosstalk and loss [11].…”
Section: Introductionmentioning
confidence: 99%